Primary Health Care And Referral Services - Reddaiah V.P; Lobo J; Kapoor S.K (Wolters Kluwer Medknow Publications, 1986)
This study is based on the analysis of morbidity attending the Casualty Service at C.R.H.S. Project Hospital Ballabgarh Which acts as & referral center for the whole Block. The morbidity is presented by age and the need for data analysis and its utilization for provision of efficient emergency services are highlighted.